E-063 Early spinal angiography identifies arterial injury in surfer's myelopathy. (23rd July 2022) - Brown, S; Panczykowski, D; Nakagawa, K; Sun, C; Koenig, M; Tsappidi, S; Hui, F
Abstract : Introduction: Surfer's myelopathy is a rare, non-traumatic spinal cord injury affecting young, healthy novice surfers. Only 64 cases have been reported to date, and the condition is neurologically serious, with more than half of described patients remaining wheelchair-bound after six months. Growing circumstantial evidence supports a vascular mechanism of injury leading to spinal cord ischemia/infarction. However, a precise understanding of the vascular injury, predisposing anatomical features, and effective medical interventions remains elusive. This is partly because spinal angiography, the gold standard for confirming vascular pathology affecting the spinal cord, is rarely pursued acutely. The only reported case including angiographic evidence of an ischemic source was performed 4.5 months after injury. Methods: We report a case of a healthy 30-year-old male who developed acute paraplegia immediately following his first surfing lesson in Big Island, Hawaii. As part of his workup and treatment, he was flown urgently to our Neuroscience ICU in Honolulu and underwent acute spinal angiography within 10 hours from injury. Results: Angiography demonstrated disconnection of the right radicular artery at T12 to the anterior spinal artery (ASA). The left T12 radicular artery feeds across midline to the right T12 arcade to supply the artery of Adamkiewicz (AKA). The craniad ASA did not fill from the AKA. Given that pre-injury imaging was not available, it is uncertain whether the right T12 radicular artery directly connected with the AKA at baseline. However, the non-filling of the craniad ASA despite full spinal angiography suggests ASA occlusion from arterial injury. Conclusion: Surfer's myelopathy is a rare, non-traumatic spinal cord injury without any known medical interventions, resulting in complete paraplegia in over 50% of cases. Our patient represents the first reported case undergoing acute spinal angiography, which revealed anterior spinal artery compromise. This case supports an arterial pathophysiology underlying surfer's myelopathy, offering valuable insight into potential acute interventions. Disclosures: S. Brown: None. D. Panczykowski: None. K. Nakagawa: None. C. Sun: None. M. Koenig: None. S. Tsappidi: None. F. Hui: None.